1990
DOI: 10.1037/0735-7044.104.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal proximity on behavioral and physiological responses to separation in infant rhesus monkeys (Macaca mulatta).

Abstract: The effects of maternal proximity on the behavioral and physiological responses of infant rhesus macaques during 4 days of total or adjacent separations from the mother were studied. The 6 infants tested showed behavioral responses that differentiated the two separation conditions. Major differences were found in the quantity and quality of vocalizations, the occurrence of cage-biting and cage-shaking behavior, object exploration, and hunched and freezing postures. In particular, the structure of coo vocalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 19 publications
(19 reference statements)
7
58
1
Order By: Relevance
“…Maternal presence has a strong regulatory influence on the ANS and HPA axis in rodents and primates (11,43), and insecure attachment is associated with elevated cortisol reactivity and vagal withdrawal in young children (44,45). Moreover, placement before 24 months in BEIP is also associated with substantially greater odds of developing a secure attachment (42), indicating a similar sensitive period for attachment security as we observe for cortisol reactivity and vagal regulation.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Maternal presence has a strong regulatory influence on the ANS and HPA axis in rodents and primates (11,43), and insecure attachment is associated with elevated cortisol reactivity and vagal withdrawal in young children (44,45). Moreover, placement before 24 months in BEIP is also associated with substantially greater odds of developing a secure attachment (42), indicating a similar sensitive period for attachment security as we observe for cortisol reactivity and vagal regulation.…”
Section: Discussionsupporting
confidence: 57%
“…Rhesus and squirrel monkeys exposed to prolonged early-life maternal deprivation exhibit elevated basal levels of cortisol (7-9), enhanced glucocorticoid feedback sensitivity (10), and heightened cortisol reactivity to social stress in some studies (11,12), but lower basal cortisol and reduced cortisol reactivity in others (9,13,14). The effect of maternal deprivation on SNS development in nonhuman primates has been studied infrequently.…”
mentioning
confidence: 99%
“…Normal infants physically separated from their mothers respond with species-typical protest behaviors (Sackett, 1970;Bayart et al, 1990) and immediately seek proximity to their mothers (Sackett et al, 1967;Suomi et al, 1973Suomi et al, , 1983. Furthermore, separation paradigms in which the mother is visible but not physically accessible, such as in the mother preference test used in this study, provoke severe behavioral distress responses, as indicated by increased vocalizations (Seay and Harlow, 1965;Levine et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for sertraline's loss of effectiveness, consistent with our hypotheses, is that stress overrode the pharmacological effects of sertraline. In primates, social stress increases CNS serotonin turnover rate (Bayart et al 1990). This is particularly true during aggressive encounters (Higley et al 1996a).…”
Section: J Higley Et Almentioning
confidence: 99%